The impact of transformational leadership style and work environment on employee performance - Darmadi Darmadi; Guruh Dwi Pratama; Noto Susanto; Juwita Ramadani Fitria (Journal of Economics and Business Letters, 2023)
This study aims to determine the effects of Transformational Leadership Style and work environments on employee performance at CV. Mitra Rajaya, both individually and collectively. The method employed is a quantitative approach with a descriptive focus. Random sampling was used to select a sample of 96 respondents. Data analysis involved validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The findings show that Transformational Leadership Style has a significant impact on employee performance, as does the work environment. Additionally, Transformational Leadership Style and the work environment collectively have a significant influence on employee performance. The correlation coefficient value, indicating the strength of the relationship between the independent and dependent variables, is 0.833, signifying a strong relationship. The coefficient of determination, which represents the combined influence, is 0.694 or 69.4%, with other factors accounting for the remaining 30.6%.